2006
DOI: 10.1182/blood-2005-05-1771
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine phosphorylation modulates binding preference to cyclin-dependent kinases and subcellular localization of p27Kip1 in the acute promyelocytic leukemia cell line NB4

Abstract: We have investigated the role of tyrosine phosphorylation of the cyclin-dependent kinase (cdk) inhibitor p27 Kip1 using the acute promyelocytic leukemia cell line NB4 together with granulocyte colonystimulating factor (G-CSF). Short-term G-CSF stimulation resulted in a rapid tyrosine dephosphorylation of p27 Kip1 accompanied by a change in its binding preferences to cdks. On G-CSF stimulation, p27 Kip1 dissociated from cdk4 and associated with cdk2. Binding assays with recombinant p27 Kip1 confirmed that tyros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 28 publications
1
36
0
Order By: Relevance
“…The discovery that p27 can be phosphorylated at tyrosine residues suggested a direct link between p27 and mitogen-induced signal transduction. [61][62][63] This link is supported by the observation that tyrosine phosphorylation of p27 is increased in G 1 phase and by mitogens. 63,64 Initially, the non-receptor kinases Lyn, Src, Yes, Abl and BCR-Abl were identified as tyrosine kinases that can phosphorylate p27.…”
Section: Control Of P27 Stabilitysupporting
confidence: 61%
“…The discovery that p27 can be phosphorylated at tyrosine residues suggested a direct link between p27 and mitogen-induced signal transduction. [61][62][63] This link is supported by the observation that tyrosine phosphorylation of p27 is increased in G 1 phase and by mitogens. 63,64 Initially, the non-receptor kinases Lyn, Src, Yes, Abl and BCR-Abl were identified as tyrosine kinases that can phosphorylate p27.…”
Section: Control Of P27 Stabilitysupporting
confidence: 61%
“…28,2008 PKB PROMOTES p27-CYCLIN D1-Cdk4 ASSEMBLY 6463 appropriate antibodies, and the heat-stable cellular p27 was released from the immunoprecipitates by boiling in assembly buffer. Recovered p27 was titrated to ensure that equivalent p27 amounts were added to reaction mixtures, and their abilities to assemble recombinant cyclin D1-Cdk4 were then assayed as described above.…”
Section: Methodsmentioning
confidence: 99%
“…When differences in the expression levels of the p27 variants were VOL. 28,2008 PKB PROMOTES p27-CYCLIN D1-Cdk4 ASSEMBLY 6465…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that overexpression of c-Abl in eukaryotic cells promotes p27 KIP1 phosphorylation on tyrosine residues [35] therefore, the potential involvement of c-Abl in p27 KIP1 tyrosine phosphorylation in neuroblastoma cell lines was investigated. To do this, neuroblastoma cells were transfected with siRNAs to c-Abl.…”
Section: Discussionmentioning
confidence: 99%